Optimalisasi Ruang Terbuka Hijau Melalui Aksi Penanaman Pohon - Sativani Hayati, Riza; Irmawanty, Irmawanty; Mahmudah, Rafiah; Thahir, Rahmatiah; Hambali, Hilmi; Anisa, Anisa; Magfirah, Nurul; Fadhilah, Nurul; Wajdi, Muhammad; Nurdiyanti, Nurdiyanti; Safitri, Dian (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This tree-planting activity was conducted in response to increasing environmental degradation and the decline of green open spaces caused by rapid development and unsustainable exploitation of natural resources. The activity took place on 27 September 2025 at the Education and Training Center Area of Universitas Muhammadiyah Makassar, Bollangi, Gowa Regency, South Sulawesi, with the aim of transforming underutilized land into a productive green area with both ecological and economic value. The implementation consisted of two stages: preparation and planting of 200 fruit tree seedlings, including durian, soursop, jackfruit, and crystal guava. The results show that all seedlings were successfully planted in locations appropriate for soil conditions and sunlight exposure, supported by active participation from the participants throughout all stages. The activity not only contributed to increasing green coverage but also enhanced participants’ understanding and environmental awareness through brief training and education. Ecologically, the fruit trees planted have the potential to support carbon absorption, improve air quality, strengthen soil stability, and promote biodiversity. Economically, these trees hold promising value as future sources of marketable fruits and local food diversification. Therefore, this tree-planting initiative can be considered a long-term environmental and economic investment aligned with the principles of sustainable development.